Refrigeration - Cecil Johnson (Cengage Learning, Inc, 2006)
This "how-to" lab book creatively combines both theory and practical application into an organized system for learning about domestic and commercial refrigeration equipment. Ideal for use as a stand-alone manual or alongside any HVAC publication, this versatile guide offers brief theory lessons of what is to be learned followed by practical competencies that take readers step-by-step through specific procedures. These opportunities for "hands-on" application of key concepts help readers better understand common service, repair, and maintenance procedures. The flexible format affords users the unique opportunity to learn domestic and commercial refrigeration fundamentals and applications either on an individual basis or in an instructional setting